Web Literacy for Student Fact-Checkers - Caulfield, Mike (Open textbook library., 2017)
The web gives us many such strategies and tactics and tools, which, properly used, can get students closer to the truth of a statement or image within seconds. For some reason we have decided not to teach students these specific techniques. As many people have noted, the web is both the largest propaganda machine ever created and the most amazing fact-checking tool ever invented. But if we haven't taught our students those capabilities is it any surprise that propaganda is winning? This is an unabashedly practical guide for the student fact-checker. It supplements generic information literacy with the specific web-based techniques that can get you closer to the truth on the web more quickly.